THE RELATIONSHIP BETWEEN THE BIG FIVE PERSONALITY FACTORS AND STRESS IN MASTER’S STUDENTS IN PSYCHOLOGY AT RAMKHAMHAENG UNIVERSITY - เกตุแก้ว, วรัญญา; คงกระพันธ์, เอื้อทิพย์ (Primary Health Care Journal (Northeastern Edition), 2024)
This descriptive research aimed to study the relationship between the Big Five personality traits and stress among Master's degree students in the Master of Science in Psychology program, Faculty of Education, Ramkhamhaeng University. The sample consisted of 66 Master's students from the aforementioned program, selected through simple random sampling. The research instruments included a Big Five Personality Traits Scale with a reliability of 0.88 and a Stress Assessment Scale from the Stress Relief Handbook (revised version), published by the Department of Mental Health in 2012. Data were analyzed using descriptive statistics, including frequency distribution, mean, and standard deviation, as well as Pearson’s correlation coefficient to examine relationships, with statistical significance set at the .05 level. The results showed that the sample had high levels of personality traits related to extraversion, openness to experience, agreeableness, and conscientiousness, while they had low levels of neuroticism. Both male and female students exhibited normal levels of stress. Students majoring in counseling psychology and those enrolled in the bi-semester learning format experienced mild stress. The study found a moderate positive correlation between neuroticism and stress, which was statistically significant at the .05 level. Conversely, there was a low negative correlation between agreeableness and stress, also statistically significant at the .05 level. Based on these findings, the program should consider developing an educational plan that fosters agreeableness and openness to experience to help reduce student stress.